ANALISIS KEBUTUHAN LUAS LAHAN BASAH PERTANIAN PANGAN DALAM PEMENUHAN KEBUTUHAN PANGAN PENDUDUK KABUPATEN LAMPUNG BARAT - Sumarlin Sumarlin; Yayuk Farida Baliwati; Ernan Rustiadi (Jurnal Gizi dan Pangan, 2008)
The general objective of this research was to analyze food agriculture wet land size requirement in fulfilling food requirement of population in West Lampung District. This research was conducted by using retrospective design and secondary data which then analyzed descriptively. The research used some data, it was : 1) demography data year 2001-2007 from Central Bureau of Statistics, 2) food balance sheet data year 2007 from Food Security Board of West Lampung District, 3) food consumption data year 2007 from Agriculture and Food Security Office of Lampung Province, 4) production data, productivity data, and plant index year 2002-2007 from Crops and Horticulture Office of West Lampung District, and 5) land potential of food agricultural development year 2004 from National Survey and Mapping Coordination Board. The result of the research indicates that rice requirement in West Lampung District until year 2012 can be fulfilled by production with wet land size utilized for rice planting in 2007 (13 320 hectar) and production 103 711 ton dry harvest.